Cointegration of Islamic stock indices: evidence from five ASEAN countries - Saiti, Buerhan (IJSER, 2015)
This paper investigates the dynamic causal linkages in the daily returns among five ASEAN Shariahcompliant indices (such as, FTSEMY index, MSSNGIL index, JAKSEIS index, MSTHFIL index and MSPHISL index) through the application of the standard time series techniques. Essentially, the purpose of this research is to identify the extent of linkages of Islamic stock indices in five ASEAN countries. Our study is focused on investigating the following empirical questions: (i) are these selected five Shariah-compliant stock indices cointegrated? and (ii) which major stock index was driving the selective Shariah-compliant stock indices? Our findings tend to suggest: (i) the selected Islamic stock indices appear to have a theoretical and long-run comovement (as evidenced in the Cointegration and LRSM tests) (ii) Finally, what stands out is the leadership of the Malaysia Shariah stock index in driving all Islamic stock indices (as evidenced in the VDCs tests).